2020
DOI: 10.1101/2020.11.26.20239046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence and prognostic factors of knee extension deficits following anterior cruciate ligament reconstruction: A systematic review and meta-analysis of randomised controlled trials

Abstract: Background and aimsKnee extension deficits complicate recovery from ACL injury and reconstruction, however the incidence of knee extension loss is not well defined. The aim of this review was to identify the incidence of loss of extension (LOE) following ACL rupture and reconstruction, explore the definitions of knee extension deficits reported and identify prognostic factors affecting LOE incidence.Methods and analysisA systematic search was conducted in Medline, Cochrane Library and PEDro for studies in publ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Non-inferiority was declared if the upper limit of the one-sided 97.5% confidence interval for the marginal estimate of LOE Incidence in the SGTS group did not exceed a relative difference of 30% from the baseline incidence of the non-SGTS group (risk-ratio 1.3), equivalent to a one-sided test with an alpha of 0.025 [28]. The non-inferiority margin was derived from a related systematic review [10] which identified a median baseline incidence of LOE 0.16 at a median of 4.9 months post ACLR. A 10% absolute increase in patients presenting with LOE given the new technique above the rate seen with the existing techniques was deemed clinically acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…Non-inferiority was declared if the upper limit of the one-sided 97.5% confidence interval for the marginal estimate of LOE Incidence in the SGTS group did not exceed a relative difference of 30% from the baseline incidence of the non-SGTS group (risk-ratio 1.3), equivalent to a one-sided test with an alpha of 0.025 [28]. The non-inferiority margin was derived from a related systematic review [10] which identified a median baseline incidence of LOE 0.16 at a median of 4.9 months post ACLR. A 10% absolute increase in patients presenting with LOE given the new technique above the rate seen with the existing techniques was deemed clinically acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…A trial protocol was developed to assess the validity of this new and unique hip navigation system in measuring acetabular cup inclination, acetabular cup version, femoral offset and leg length discrepancy (Ektas, Scholes, Harrison-Brown, et al, 2020). This study reports the accuracy of the device by comparing intraoperative component positioning to postoperative CT measurements, specifically in patients undergoing THA using an anterolateral approach in the lateral decubitus position.…”
Section: Introductionmentioning
confidence: 99%